Luminescent sequence-dependent materials through a step by step assembly of RE1–1, 4-benzendicarboxylate–RE2 (REx = Y3+, Eu3+ and Tb3+) architectures on a silica surface. Issue 15 (21st March 2019) - Bellucci, Luca; Bottaro, Gregorio; Labella, Luca; Marchetti, Fabio; Samaritani, Simona; Belli Dell'Amico, Daniela; Armelao, Lidia
Abstract : Stepwise assembly on a silica surface of ordered sequences of rare earth cations (Y 3+, Eu 3+, Tb 3+ ) connected by the 1, 4-benzenedicarboxylate ligand affords sequence-dependent luminescence properties. Abstract : We present an approach toward sequence-dependent materials based on a stepwise assembly on a silica surface of rare earth cations (RE: Y 3+, Eu 3+ and Tb 3+ ) and the 1, 4-benzenedicarboxylate (terephthalate, T 2− ) ligand, organized in an ordered sequence RE 1 –T–RE 2 . The first RE was grafted to silica through a reaction of its N, N -dibutylcarbamato derivative, [RE 1 (O2 CNBu2 )3 ], with the surface silanols. The residual carbamato groups in the metal coordination sphere were then substituted by HT − through a reaction with H2 T in pyridine. The Brønsted acidity of the pendant COOH groups was successively exploited for the anchorage of the second metal ion (RE 1 = Eu, RE 2 = Tb; RE 1 = Y, RE 2 = Tb). The choice of pyridine as the solvent, able to dissolve both H2 T and the secondary product [NH2 Bu2 ]2 [T]·H2 T, was crucial for achieving success with this method. The emission properties of the materials were modulated by modifying the order of the synthetic steps. Metal complexes and materials were characterized by IR, EDX, ICP and photoluminescence. We used Tb 3+ to Eu 3+ energy transfer (ET) to study the RE 3+ spatial distribution and intermetal distances to prove the formation of a RE 1 –T–RE 2 sequence. Photoluminescence was used as a multi-tool technique to characterize the functional properties of the materials and to obtain structural information supporting the sequence growth.